Javanese and Islamic Syncretism in the Meaning of the Singo Mengkok Batik Motif by Sunan Drajat, Lamongan - Kartika Herlina Candraning Shiam (LPPM Institut Seni Indonesia Padangpanjang, 2025)
The Singo Mengkok batik motif from the time of Sunan Drajat's missionary work in Lamongan is a cultural artifact resulting from sophisticated syncretism, combining Javanese-Hindu symbolism (Padma Flower/Tunjung), Chinese (Qilin/Kirin), and Islamic values. Using Clifford Geertz's symbolic interpretation approach, this study reveals that this motif functions as a complex symbol system. At the cognitive/mythical level, the shape of the squatting lion transforms the concept of physical strength into a spiritual one, reflecting the subjugation of desires, in line with Surah Al-Qasas: 50. At the evaluative level, its isen-isen function as a visual catechism, teaching the Five Pillars of Faith, the Five Pillars of Islam, and the obligation of prayer. As a backdrop for Sunan Drajat's gamelan performances, this batik serves as an effective medium for cultural missionary work, demonstrating a wise acculturation strategy that respects local culture while harmoniously conveying Islamic teachings.